Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The reality of applying the principles of university governance at the University of Idlib  from the Perspective of Faculty MembersMr. Ahmad Mohamad Staif, Co-Prof. Siham Mustafa Abdulaziz, Dr. Hisham Farag Abd Alsid2. The reality of reflective practices in action research and its difficulties from the point of view of a random sample of primary school teachers at Umm Al-Muminin Aisha School in Al-Zulfi GovernorateMrs. Lulwah Abdullah Al-Fahd, Co-Prof. Abeer Mohammed Al-Arfaj3. Using the museum education in teaching kindergarten children  from the point of view of kindergarten teachers in Medina cityMrs. Esraa Emad Kurdi, Co-Prof. Kawther Jamil Belgoun4. The effect of using artificial intelligence applications in improving selective attention of students with learning disabilities in the primary stageMrs. Enas Attia Alghamdi , Mrs. Sahar Hamdan Alghamdi , Dr. Leena Ahmad Alfarani5. Teaching attitudes among Arabic language teachers of Arabic for non-native speakers in The Sultanate of OmanMr. Amer Salim Hamad Al-Isaee , Dr. Saif Nasser Saif Al-Azri6. Obstacles to scientific publishing in scientific journals classified within the (ISI) and (Scopus) databases from the point of view of faculty members in some universities in Arab countriesProf. Maha Abdullah Al-Dabbagh
Keywords: Journal of Educational and Psychological Sciences